The Analysis of Women’s and Men’s Language Features in Disney Movies - Sri Sapitri, Ni Komang; Laksminy, Luh Putu; Saientisna, Made Detriasmita (Humanis, 2023)
In everyday life, humans interact and communicate using language. The use of language varies depending on gender, which is influenced by the different roles each gender plays in society. The different use of language then referred to language features that it uses are also reflected in movies. This study aims to analyze the women’s and men’s language features used by the main character in Disney Movies. The data were analyzed using a descriptive qualitative method with a theory proposed by Lakoff (1975) and Coates (2004) . It was found out that the main character of the Turning Red Movie (2022) used eight forms out of ten women language features proposed by Lakoff; meanwhile, the main character in the Ron’s Gone Wrong Movie (2021) used all of the men’s language features proposed by Coates. This result shows that women and men have their characteristics in using language as a form of influence from their social environment.